Pengaruh Lingkungan Kerja Terhadap Kinerja Pegawai Pada Kantor Pengawasan Dan Pelayanan Bea Dan Cukai Tipe Madya Pabean B Pekanbaru - Herman, Herman (Eko dan Bisnis: Riau Economic and Business Review, 2022)
This study was conducted to determine the effect of the work environment on employee performance at the Customs and Excise Office of Supervision and Excise Service Type B Pekanbaru. The population in this study were all teachers at the Office of Supervision and Service of Customs and Excise Madya Customs Type B Pekanbaru totaling 109 people. Samples were taken as many as 52 people. Data analysis in this study used descriptive and quantitative analysis methods. From the descriptive analysis, it was found that the respondent's response to the Work Environment variable statement was an average of 3.76 (Agree). Furthermore, the respondent's response to the statement of performance variables is on average 3.84 (Agree). The results of simple linear regression in this study are Y = 11.205 + 0.519X. By using the t-test, the ttable value is 2.009 and the tcount value is 6.562, meaning tcount = 11.205 > ttable = 2.009, which means that the work environment affects employee performance at the Customs and Excise Supervision and Service Office of Pekanbaru Type B Customs with a large influence of 46.3 The remaining % of 53.7% is influenced by other variables not included in this study.